(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
It is important to conduct theoretical and methodological training when preparing students of pedagogical universities for pedagogical activity. The article provides information about the conditions, forms of implementation, stages of theoretical and methodological training of students. There are also trainings, games, exercises that serve to increase the effectiveness of theoretical and methodological training of students during practical classes.